Micro-nano bubble water subsurface drip irrigation affects strawberry yield and quality by modulation of microbial communities - Zhen Zheng; Yuming He; Yingli He; Jing Zhan; Chunyan Shi; Yujie Xu; Xiaowen Wang; Jian Wang; Chao Zhang (Agricultural Water Management)
Aerated irrigation can enhance soil conditions such as soil oxygen, soil temperature, and soil moisture content and alter the structure of soil microbial communities. However, there is a dearth of research on the specific mechanisms and their mutual influence. Rhizosphere soil microbes are sensitive to changes in the soil environment, and the delivery of air or oxygenated water to rhizosphere soil significantly impacts the structure of the soil microbial community. In this study, a greenhouse strawberry subsurface drip irrigation experiment with micro-nano bubble water (MNBW) was conducted, with seven different aeration treatments and one control treatment (CK). The results showed that compared to CK, the aeration treatments improved the soil conditions to varying degrees and changed the structure of the strawberry rhizosphere soil microbial community. Furthermore, the yield, vitamin C, soil oxygen content, soil temperature and soil moisture increased by an average of 108 %, 3 %, 12 %, 10 % and 4 %, respectively. The results indicated that MNBW irrigation increased the abundance of specific bacterial communities, thereby affecting strawberry yield and quality. Correlation analysis results revealed the specific mechanisms of mutual influence between soil environment and soil microbes. Therefore, AFE (aeration during the fruit expansion stage) and AB+F (aeration during both the budding stage and flowering stage) can significantly activate the microbes in the strawberry rhizosphere soil and are considered the optimal times for enhancing strawberry yield and quality through MNBW irrigation.